5. Analysis of correspondence between width of gating window and chest wall position during deep inspiration breath-hold (DIBH) for left-sided breast radiotherapy. (December 2018) - Mordacchini, C.; Angiocchi, M.C.; Nocera, P.; Novario, R.
Abstract : Purpose: Aim of our study is to verify the correspondence between gating window width and chest wall position by analysis of Respiration Waveform acquired by Varian RPM Respiratory Gating System during treatments of left-sided breast in DIBH. Methods: Two CT series were obtained for each patient, in free breathing (FB) and DIBH using RPM. In DIBH the width of the gating window, i.e. the allowed chest wall motion, was identified for each patient considering 5 mm margins and stored on Reference Respiration Waveform to be used during treatment. Respiration Waveforms acquired during 211 treatments (9 patients) were compared with proper Reference, considering the minimum point before DIBH as common origin, both in time and chest wall motion. The difference between treatment chest wall position and reference chest wall position was evaluated as difference between median values of RPM block position stored during treatment and during CT scan (plateau in graphic, Fig. 1). Results: The differences between median values of RPM block position stored during treatment and during CT scan ranged from −9.0 mm to 8.2 mm; the average value is 0.2 mm and the standard deviation is 3.3 mm. The frequency of the differences is reported inTable 1 . Conclusions: Our analysis of Respiration Waveforms acquired during treatments shows good correspondence between the chosen gating window and the variability in chest wall position in DIBH, confirming that 5 mm margins around the Reference Position is advisable to limit significant misalignments between treatment fields and patient's tissues.